Quality of life analyses in patients with multiple myeloma: results from the Selinexor (KPT-330) Treatment of Refractory Myeloma (STORM) phase 2b study - Tremblay, Gabriel; Daniele, Patrick; Breeze, Janis; Li, Lingling; Shah, Jatin; Shacham, Sharon; Kauffman, Michael; Engelhardt, Monika; Chari, Ajaj; Nooka, Ajay; Vogl, Dan; Gavriatopoulou, Maria; et al. (BMC cancer, 2021)
Selinexor is an oral, selective nuclear export inhibitor. STORM was a phase 2b, single-arm, open-label, multicenter trial of selinexor with low dose dexamethasone in patients with penta-exposed relapsed/refractory multiple myeloma (RRMM) that met its primary endpoint, with overall response of 26% (95% confidence interval [CI], 19 to 35%). Health-related quality of life (HRQoL) was a secondary endpoint measured using the Functional Assessment of Cancer Therapy - Multiple Myeloma (FACT-MM). This study examines impact of selinexor treatment on HRQoL of patients treated in STORM and reports two approaches to calculate minimal clinically important differences for the FACT-MM.